The Effect of Turbulence Weather Information on Decision-Making of Air Traffic Controllers at Jakarta ACC - Hafidz Kuncoro Jati; Surya Tri Saputra; Martha Saulina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Safe and efficient air traffic services depend on the ability of Air Traffic Controllers (ATCs) to make timely and accurate decisions, particularly when confronted with adverse meteorological phenomena such as turbulence. This study aims to analyze the influence of turbulence weather information on the operational decision-making of ATCs at the Jakarta Area Control Centre (ACC). Employing a quantitative approach, data were collected from 77 respondents through structured questionnaires and analyzed using descriptive and inferential statistics, including validity, reliability, and linear regression tests. The findings indicate a positive and significant relationship between the provision of turbulence information (independent variable) and ATC decision-making (dependent variable), with a coefficient of determination (R²) of 0.640. This result suggests that 64% of decision-making accuracy is influenced by the quality of turbulence information, while the remaining 36% is affected by other factors such as workload and experience. The study concludes that enhancing the timeliness, accuracy, and completeness of meteorological information is crucial to support ATCs in making precise and safe operational decisions under high-pressure and high-traffic conditions within the Jakarta Flight Information Region (FIR)